A Note on Bats from Camp 5, Mulu World Heritage Area, Sarawak, Malaysian Borneo - Isham, Azhar; Mohd Ridwan, A.R.; Licia, Ho; Millawati, Gani; Sarina, Mat Yasin; M.T, Abdullah (Malayan Nature Journal, 2013)
To date, there are more than 90 species of bats recorded in Borneo. Despite the numerous information published on the diversity of bats, it is still considered scarce especially the one on the interior part of Sarawak. A bat survey was carried out at Camp 5, Mulu World Heritage Area from 3rd until 9th April 2012. Rhinolophus affinis was recorded for the first time in Mulu World Heritage Area and this had increased the current list to 41 species of bats for the park. The data represents the first bat survey of Camp 5, Mulu World Heritage Area and this helps to increase the knowledge of the bats diversity in limestone areas in Sarawak.